2022
DOI: 10.3390/genes13101695
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and Expression Profiles of the VOZ Gene Family in Quinoa (Chenopodium quinoa)

Abstract: Vascular plant one zinc-finger (VOZ) proteins are a plant-specific transcription factor family and play important roles in plant development and stress responses. However, little is known about the VOZ genes in quinoa. In the present study, a genome-wide investigation of the VOZ gene family in quinoa was performed, including gene structures, conserved motifs, phylogeny, and expression profiles. A total of four quinoa VOZ genes distributed on three chromosomes were identified. Based on phylogenetic analysis, Cq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Research on plant breeding embraces the generation of adapted cultivars to specific environmental factors such as high drought tolerance (Serna et al, 2020) and salinity soil content (Hussain et al, 2018). This corresponds to what was reported by Shi et al (2022), who indicate that quinoa has attracted great attention as a crop, mainly because it presents a strong resistance to various adverse climatic and soil conditions, such as cold, high salinity, and drought, which allows quinoa to grow on barren soil.…”
Section: Blue Cluster (63 Key Topics)-abiotic Stress Resistance Impro...supporting
confidence: 52%
“…Research on plant breeding embraces the generation of adapted cultivars to specific environmental factors such as high drought tolerance (Serna et al, 2020) and salinity soil content (Hussain et al, 2018). This corresponds to what was reported by Shi et al (2022), who indicate that quinoa has attracted great attention as a crop, mainly because it presents a strong resistance to various adverse climatic and soil conditions, such as cold, high salinity, and drought, which allows quinoa to grow on barren soil.…”
Section: Blue Cluster (63 Key Topics)-abiotic Stress Resistance Impro...supporting
confidence: 52%
“…Interestingly, CuVOZ2 seems to be more closely related to VOZ1 proteins of dicots rather than to VOZ proteins of monocots such as rice (Figure 1B). The differentiation of VOZ1 and VOZ2 transcription factors seems to have occurred after the divergence of monocotyledons and dicotyledons (Shi et al 2022). These results indicated that CuVOZ2 might have functioned like AtVOZ2 (Figure 1B).…”
Section: Discussionmentioning
confidence: 86%
“…VOZ proteins represent a plant-specific subclass of transcription factors with pivotal functions in the modulation of plant growth and development, particularly in the realm of VOZ-mediated responses to abiotic stress [ 10 , 11 , 12 ]. The VOZ gene family has been reported in a variety of plant species [ 11 , 12 , 13 , 15 ], but there is still a lack of comprehensive studies on the function of VOZ genes in cucurbits and their response to growth, development, and abiotic stresses. Consequently, there exists a pressing need for an in-depth investigation of VOZ in cucurbits.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular plant one-zinc-finger (VOZ) transcription factor family stands out as plant-specific, found exclusively in numerous higher plants, encompassing Physcomitrella patens and vascular plants [ 9 , 10 ]. VOZ was identified as a multifunctional gene that regulated various biological processes, including flower induction, development, and responses to diverse stresses [ 11 , 12 , 13 , 14 ]. Initially identified in Arabidopsis thaliana , this gene family comprised two members, namely AtVOZ1 and AtVOZ2 , which both demonstrated binding affinity to the GCGTNx7ACGC palindromic sequence during in vitro studies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation